Implementasi Jaminan Kesehatan Pasien di Semarang Berdasarkan Undang-Undang BPJS - Vilyasari, Linda; Saputra , Arikha (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
The purpose of study can be need for comparisons between regulations and what happened in the field in order to find out the good or bad implementation of health insurance and legal protection for BPJS's participants in Semarang. In this study, the writer use empirical juridical research methods, namely legal research about the enactment or implementation of normative legal provisions in each particular legal event that happen in society. BPJS or social health insurance administration body has been going on and the community has felt the benefit of BPJS, but there are still some obstacles and problems that happen in Semarang, Middle Java. Article 2 of Law Number 24 of 2011 about BPJS consist of three principles in the service of BPJS participants, including: humanity, benefit and social justice for all Indonesians. The result of the study show the implementation of health insurance in Semarang have been appropriate with Law Number 24 of 2011 about BPJS. The obstacles that consist in the implementation of health insurance in the form of internal and external constraints. ___ Referensi Buku dengan penulis: Abu Achmadi dan Cholid Narbuko. (2001). Metode Penelitian, Jakarta: Bumi Aksara. Djamin Djanius dan Syamsul Arifin. (1993). Bahan Dasar Hukum Asuransi, Medan: Badan Penerbit STIE Tri Karya. H. Mashudi dan Chidir Ali. (1995). Hukum Asuransi, Bandung: Mandar Maju. Lalu Husni. (2003). Pengantar Hukum Ketenagakerjaan Indonesia, Jakarta: PT Rajagrafindo Persada. Nidya, K. (2018). Implementasi Asas Kemanusiaan Dalam Pelayanan Terhadap Peserta Badan Penyelenggaraan Jaminan Sosial (BPJS) Kesehatan Ditinjau dari Undang-Undang Nomor 24 Tahun 2011 Tentang Badan Penyelenggaraan Jaminan Kesehatan (Doctoral dissertation, Universitas Andalas). Suteki dan Galang Taufani. (2020). Metodologi Penelitian Hukum. Depok: Rajawali Pers. Artikel jurnal: Meutia, B. I. (2020). Implementasi Pelayanan Kesehatan Menurut Undang-Undang No. 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial (BPJS) (Studi di RSUD Kertosono Kabupaten Nganjuk). Legal Spirit, 4(1). Rinaldo, R. R., Pujiastuti, E., dan Sukimin, S. (2022). Implikasi Pengaturan Sistem Rujukan Berjenjang Terhadap Pelayanan Kesehatan Perorangan. Semarang Law Review (SLR), 1(1), 1-15. Widada, T., Pramusinto, A., dan Lazuardi, L. (2017). Peran Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan dan Implikasinya terhadap Ketahanan Masyarakat (Studi di RSUD Hasanuddin Damrah Manna Kabupaten Bengkulu Selatan, Provinsi Bengkulu). Jurnal Ketahanan Nasional, 23(2), 199-216.